2010
DOI: 10.2495/st100351
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic of Boon Kam Fa tradition of Phuan Ethnic Group in the Thailand tourism context

Abstract: The purpose of this research

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Studies of the kam fa festival have found tourist events to be laden with prejudices of the Phuan people that are not consistent with inherited traditions. Although these have contributed to the success of the festival by tapping into tourist attraction to 'otherness', they do not present a true picture of the Phuan people (Aneksuk & Ruangkamnerd, 2010). Domestic scholarship has overwhelmingly emphasised the need for local adaptation to tourist demand to facilitate an improved tourism experience that will in turn stimulate conservation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the kam fa festival have found tourist events to be laden with prejudices of the Phuan people that are not consistent with inherited traditions. Although these have contributed to the success of the festival by tapping into tourist attraction to 'otherness', they do not present a true picture of the Phuan people (Aneksuk & Ruangkamnerd, 2010). Domestic scholarship has overwhelmingly emphasised the need for local adaptation to tourist demand to facilitate an improved tourism experience that will in turn stimulate conservation.…”
Section: Discussionmentioning
confidence: 99%
“…Slow integration has been caused by a lack of cooperation between the Phuan people and government institutions, with fault on both sides. Some government officials have been accused of hostility towards the ethnic group, whilst some Phuan people have refused assistance from mainstream organisations (Aneksuk & Ruangkamnerd, 2010). There should not be a top-down organisation of cultural activities.…”
Section: Discussionmentioning
confidence: 99%